Engineering design of lossless passive soft switching methods for PWM converters. I. With minimum voltage stress circuit cells. - Smith, K.M., Jr (IEEE Transactions on power electronics)
This paper presents the analysis and design methodology of lossless passive soft switching converters from an engineering perspective. The circuit operation and soft switching loss analysis are detailed and an intuitive procedure is derived that enables quick and accurate design. Analysis is given for a set of soft switching circuit cells with minimum switch voltage stress used to synthesize a family of soft switching converters. The design is based on minimizing switching losses while maintaining soft switching over the desired operating range. A new simple loss model is derived to optimize the values of the resonant components for a particular design. As an example of the design procedure, a PFC boost converter is designed and tested